Impact of the host response and osteoblast lineage cells on periodontal disease - Zhou, Mi; Graves, Dana T. (Frontiers in Immunology, 2022)
Periodontitis involves the loss of connective tissue attachment and alveolar bone. Single cell RNA-seq experiments have provided new insight into how resident and infiltrating immune cells function in response to bacterial challenge in periodontal tissues. Periodontal disease is induced by a combined innate and adaptive immune response to bacterial dysbiosis that is initiated by resident cells including epithelial cells and fibroblasts, which recruit immune cells. Chemokines and cytokines stimulate recruitment of osteoclast precursors and osteoclastogenesis in response to TNF, IL-1β, IL-6, IL-17, RANKL and other factors. Inflammation also suppresses coupled bone formation to limit repair of osteolytic lesions. Bone lining cells, osteocytes and periodontal ligament cells play a key role in both processes. The periodontal ligament contains cells that exhibit similarities to tendon cells, osteoblast-lineage cells and mesenchymal stem cells. Bone lining cells consisting of mesenchymal stem cells, osteoprogenitors and osteoblasts are influenced by osteocytes and stimulate formation of osteoclast precursors through MCSF and RANKL, which directly induces osteoclastogenesis. Following bone resorption, factors are released from resorbed bone matrix and by osteoclasts and osteal macrophages that recruit osteoblast precursors to the resorbed bone surface. Osteoblast differentiation and coupled bone formation are regulated by multiple signaling pathways including Wnt, Notch, FGF, IGF-1, BMP, and Hedgehog pathways. Diabetes, cigarette smoking and aging enhance the pathologic processes to increase bone resorption and inhibit coupled bone formation to accelerate bone loss. In other bone pathologies e.g. rheumatoid arthritis, post-menopausal osteoporosis and bone unloading/disuse, osteoblast lineage cells also participate in formation of osteolytic lesions by promoting bone resorption and inhibiting coupled bone formation.